2020
DOI: 10.36953/ecj.2020.21311
|View full text |Cite
|
Sign up to set email alerts
|

Selected blood parameters altered by different doses of pesticide Malathion in albino rat (Rattus-norvegicus)

Abstract: Organophosphate pesticides Malathion used as pest control agent in agriculture, household, kitchen and other places. Malathion is found in market with different trade names. It is used with its action properties against various insects and pest. It is used with the largest group of poisonous substances that are widely broadcast today. Present study is based on the effects of different doses of Malathion on routine hematological parameters like RBCs, WBCs, Hb%, CT, PT, ESR, PCV, MCV, MCH, and MCHC. Four doses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Additionally, WBCs and neutrophils increased in the SFX-intoxicated group, while lymphocytes, eosinophils, monocytes, and basophils decreased. These results are consistent with the findings of (Sharma et al, 2020), who reported that while WBC count increased after a single dosage of chlorpyrifos, RBCs, hemoglobin, and decreased.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, WBCs and neutrophils increased in the SFX-intoxicated group, while lymphocytes, eosinophils, monocytes, and basophils decreased. These results are consistent with the findings of (Sharma et al, 2020), who reported that while WBC count increased after a single dosage of chlorpyrifos, RBCs, hemoglobin, and decreased.…”
Section: Discussionsupporting
confidence: 92%
“…PCV readings are important in determining the effect of pesticides and in determining the oxygen-carrying capacity of the blood. Previous studies [ 14 , 19 24 ] found a similar decrease in TEC and Hb in malathion and nitrobenzene-exposed animal models.…”
Section: Discussionsupporting
confidence: 66%